[LB.03.01] AGE-DEPENDENT SYMPATHETIC NEURAL RESPONSES TO BETA-1 SELECTIVE BETA-BLOCKADE IN UNTREATED HYPERTENSION-RELATED TACHYCARDIA. (September 2017) - Hering, D.; Kucharska, W.; Czechowicz, K.; Chrostowska, M.; Narkiewicz, K.
Abstract : Objective: Elevated heart rate (HR) has been linked to cardiovascular morbidity and mortality in hypertension. The impact of beta-blockers on tachycardia-related prognosis in hypertension is controversial. The mechanisms underlying therapy with β-1 selective blocking agent without intrinsic sympathomimetic activity in hypertension are unknown. This study examined the age-related effects of betaxolol on HR, muscle sympathetic nerve activity (MSNA), blood pressure (BP) and sympathovagal balance in untreated patients with hypertension and tachycardia. Design and method: Ten young (age 26 ± 1 years, BMI 25 ± 1 kg/m 2 ) and 7 older (age 50 ± 4 years, BMI 30 ± 2 kg/m 2 ) males underwent measurement of office BP and HR, HR variability (Poincare plot) and MSNA (microneurography) before and after an 8-week treatment with betaxolol at an initial dose of 10 mg/day once daily, titrated to 20 mg/day at week 4. Results: In younger subjects, betaxolol decreased systolic BP (−13 ± 4 mmHg, P = 0.01) and HR (−29 ± 4 bpm, P < 0.001) but not MSNA (3 ± 3 burst/min., P = 0.47) after 8 weeks. In contrast, in older subjects a pronounced reduction in BP (−27 ± 7, P = 0.007) was accompanied by a significant decrease in MSNA (−13 ± 5 burst/min., P < 0.05) and HR (−17 ± 4 bpm, P = 0.002). There was a comparable decrease in diastolic BP in young (−14 ± 3 mmHg, P < 0.001) and older (−14 ± 3 mmHg, P = 0.003) males. SD1/SD2 ratio of Poincare plot increased in younger (0.36 ± 0.03 vs 0.51 ± 0.05, P = 0.004), but not in older (0.43 ± 0.08 vs 0.54 ± 0.12, P = 0.50) patients. Conclusions: The autonomic neural responses to betaxolol are age-dependent in hypertension-related tachycardia. Chronic therapy with betaxolol reduces sympathetic drive to the heart, but not to the vessels confirming the contribution of augmented cardiac sympathetic activity to disease pathophysiology in younger adults. In older hypertensives, the sympathovagal balance on the heart level is not influenced by betaxolol. The paradoxical reduction in sympathetic outflow to the peripheral vessels despite lowering of BP and HR may suggest age-related functional decrements in autonomic control (e.g. downregulation of cardiac β-1 adrenoreceptors, baroreflex impairment) or specific properties of betaxolol, possibly associated with inhibition of the central nervous system.